2020
DOI: 10.1371/journal.pone.0233727
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of occult hepatitis B in high-risk populations in Kenya

Abstract: Occult hepatitis B infection (OBI) is defined as the presence of hepatitis B virus (HBV) DNA in the liver or serum in the absence of detectable HBV surface antigen (HBsAg). OBI poses a risk for the development of cirrhosis and hepatocellular carcinoma. The prevalence of OBI in Kenya is unknown, thus a study was undertaken to determine the prevalence and molecular characterization of OBI in Kenyan populations at high risk of HBV infection. Sera from two Nairobi cohorts, 99 male sex workers, primarily having sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…The prevalence is however low compared to a prevalence of between 8.3% to 30.8% Table 3 Drug resistance conferring mutations from the current study These mutations were identified using two online tools Geno2Pheno HBV database (HBVdb) (https ://hbv.geno2 pheno .org/) and HBVseq program from HIV Stanford database (https ://hivdb .stanf ord.edu/HBV/HBVse q/devel opmen t/HBVse q.html). The mutations are listed for each of the sample where they occurred reported by Jepkemei et al [37] among different high risk groups of HBV infection [37]. Majority of the mutations in the P gene described in this study were primary drug resistance mutations that decrease susceptibility to nucleoside analogues.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The prevalence is however low compared to a prevalence of between 8.3% to 30.8% Table 3 Drug resistance conferring mutations from the current study These mutations were identified using two online tools Geno2Pheno HBV database (HBVdb) (https ://hbv.geno2 pheno .org/) and HBVseq program from HIV Stanford database (https ://hivdb .stanf ord.edu/HBV/HBVse q/devel opmen t/HBVse q.html). The mutations are listed for each of the sample where they occurred reported by Jepkemei et al [37] among different high risk groups of HBV infection [37]. Majority of the mutations in the P gene described in this study were primary drug resistance mutations that decrease susceptibility to nucleoside analogues.…”
Section: Discussionmentioning
confidence: 70%
“…conducted later on who reported a prevalence of 2.25% of OBI among HIV patients [ 35 , 36 ]. The prevalence is however low compared to a prevalence of between 8.3% to 30.8% reported by Jepkemei et al [ 37 ] among different high risk groups of HBV infection [ 37 ].…”
Section: Discussionmentioning
confidence: 79%
“…Across the region, prevalence of HBV was approximately similar in Co ˆte d'Ivoire, Burkina Faso and Mali with a prevalence of 8.5% among PLHIV [23]. Among FSW, a study in South African found a prevalence of 4% in 2017 and another one in Kenya a prevalence of 10.1% in 2020 [6,24]. Those results…”
Section: Discussionmentioning
confidence: 63%
“…This was lower than the 18.7% described by Jepkemei et al in a Kenyan study of a heterogeneous population of individuals at high risk of HBV infection, some of whom were HIV positive and on anti-retroviral therapy. This was mainly driven by the high prevalence among patients with symptomatic liver disease, who made up more than a third of the study population [19]. This prevalence is also much lower than what is described in other sub-Saharan countries where it ranges from 15.1 to 24% among the HIV infected [9,10,14,20].…”
Section: Discussionmentioning
confidence: 77%